Implementasi Model Pembelajaran Diskusi (Discussion Based Learning) terhadap Keterampilan Komunikasi Siswa - Puspita, Iis (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to determine the implementation of the discussion based learning model on students' communication skills. This study was conducted in class XI of SMA Negeri 5 Maluku Tengah in the even semester of the 2023/2024 academic year, with 47 students as respondents. This type of research is a quasi-experiment using two classes, namely the experimental class and the control class. The experimental class uses a discussion based learning model, while the control class uses a conventional learning model. The instrument used in this study was an observation sheet. Data analysis of communication skills used a 5-point Likert scale with categories of very low, low, medium, high, and very high. Based on the results of the analysis of the communication skills observation sheet that had been carried out, an average value of communication skills was obtained of 69% with a high category. The implication of this study is that the discussion based learning model can be an alternative to improve students' communication skills.